Thermal Mismatch Effect and High-Temperature Tensile Performance Simulation of Hybrid CMC and Superalloy Bolted Joint by Progressive Damage Analysis - Shuyuan Zhao; Jianglong Dong; Chao Lv; Zhengyu Li; Xinyang Sun; Wenjiao Zhang (International Journal of Aerospace Engineering)
The hybrid CMC and superalloy bolted joints have exhibited great potential to be used as thermostructural components of reusable space transportation systems, given the respective strengths of these two materials. In the high temperature excursion of the hybrid joints with the aircrafts and space vehicles, the substantial difference in thermal expansion coefficients of CMC and superalloy materials will induce complex superposition of initial assembly stress, thermal stress, and tensile stress around fastening area, which might lead to unknown failure behavior of joint structure. To address this concern, a finite element model embedded with progressive damage analysis was established to simulate the thermostructural behavior and high-temperature tensile performance of single-lap, single-bolt C/SiC composite and superalloy joint, by using the ABAQUS software. It was found that the initial stiffness of the CMC/superalloy hybrid bolted joints decreases with the rise of applied temperature under all bolt-hole clearance levels. However, the load-bearing capacity varies significantly with the initial clearance level and exposed temperature for the studied joint. The thermal expansion mismatch generated between the CMC and superalloy materials led to significant changes in the assembly preload and bolt-hole clearance as the high-temperature load is applied to the joint. The evolution in the thermostructural behavior upon temperature was then correlated with the variations in stiffness and failure load of the joints. The provided new findings are valuable for structural design and practical application of the hybrid CMC/superalloy bolted joints at high temperatures in next-generation aircrafts.